Impact of Coma Duration on Functional Outcomes After Septic Encephalopathy: A Literature Review - Shafitri, Shira Shalsabina; Sugiono, Muhammad Rafly Adrian; Paradiesta, Andi Frieskha Naurah; Aulia, Siti Zahroni; Ilmiah, Janiya Abdila; Hunaifi, Ilsa (Jurnal Biologi Tropis, 2025)
Sepsis-associated encephalopathy (SAE) is a neurological complication often found on sepsis patients and is associated with high morbidity and mortality rates. It arises from systemic inflammation, blood-brain barrier disruption, microglial and astrocytic activation, and oxidative stress which collectively contribute to neuronal injury and long-term cognitive impairment. This literature review aims to analyze the impact of coma duration on functional outcomes at discharge and long-term survival among patients with SAE. Literatures were searched through PubMed, ScienceDirect, and Google Scholar with a 10-year publication limit and selected based on topic relevance, study design, and data completeness and were analyzed using a narrative synthesis approach. Findings indicate that prolonged coma duration is strongly associated with poor neurological recovery, increased risk of disability, and early mortality. Conversely, early recovery of consciousness tends to correlate with better short-term functional outcomes. However, among survivors discharged from intensive care, coma duration doesn’t consistently predict long-term survival, although cognitive and quality of life impairments often persist. In conclusion, coma duration serves as an important prognostic factor in SAE, but it should be interpreted alongside other factors such as age, comorbidity, and the severity of sepsis itself. The scientific implications highlight the need for , infection control, and rehabilitative strategies to shorten periods of altered consciousness and improve neurological outcomes in the long term.